Ziarah Sebagai Instrumen Silaturahmi: Analisis Semantik Hadis Perspektif Toshihiko Izutsu - Rizky Sulaiman; Hawwin Huda Yana; Nurdiana Sari; Dedi Andrianto (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study analyzes the conceptual relationship between ziarah (visiting) and silaturahmi (maintaining kinship ties) from the perspective of hadith and reconstructs the meaning of ziarah which has undergone semantic reduction among contemporary Indonesian Muslim society. Using a qualitative approach with library research method, this study applies Toshihiko Izutsu's semantic analysis, distinguishing between basic meaning and relational meaning. Primary data sources include major hadith collections such as Shahīh al-Bukhārī, Shahīh Muslim, and Sunan al-Tirmidzī. The findings reveal that the relationship between ziarah and silaturahmi is instrumental-normative: ziarah serves as an instrument of social action to actualize silaturahmi as a moral value. The basic meaning of ziarah is